Does the flutter kick exert propulsion in front crawl swimming? - Homoto, K.; Koga, D.; Tsunokawa, T.; Sengoku, Y.; Homma, M.; Takagi, H. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Among the four strokes used in competitive swimming, the front crawl can achieve the highest swimming velocity and is performed using alternating left and right arm strokes and leg kicks (the flutter kicks) (Yanai & Wilson, 2008). The use of the flutter kicks increased swimming velocity by 10% over the no-kick condition in front crawl (Gourgoulis et al., 2014; Silveira et al., 2017). However, the reason why the flutter kicks improve swimming velocity has been somewhat unclear. Swimming velocity is determined by the propulsion exerted by the swimmer and the drag force acting on their body. Therefore, by using the flutter kicks, the swimming velocity is improved as a result of either the increased propulsion or reduced drag force. A study investigating active drag during front crawl swimming reported that there was no difference in active drag at the same swimming velocity with or without the flutter kicks (Narita et al., 2018). Thus, the possibility of the drag force being reduced by the flutter kicks might be low, and it is likely that the use of the flutter kicks increases the total propulsion exerted by the swimmer and improves the swimming velocity. In addition, Gourgoulis et al. (2014) investigated the effect of flutter kicks on hand propulsion using quasi-static approach in maximal effort swimming. In that study, although the hand propulsion is not a measured value, but an estimated value calculated from the kinematics of the hand, there was no difference in hand propulsion. This means that the flutter kicks likely contribute directly to propulsion. To date, no studies have directly measured the propulsion of the flutter kicks. Gutta et al. (2012) towed a swimmer performing the flutter kicks with maximum effort and maintaining a streamline position various velocity, and estimated the propulsion of the from the traction force. As a result, they reported that the propulsion has measured even at a maximum of 2.0 m/s, although it decreased as the traction velocity increased. From this result, it is possible that the propulsion may be exerted even at high swimming velocity in the kick motion. However, a study that indirectly calculated propulsion using simulation also reported that the flutter kicks may not exert any propulsion (Nakashima, 2007). In this way, previous research suggests that the propulsion is likely to be exerted by the flutter kicks, but no consensus has yet been reached. In order to overcome this situation, it is necessary to investigate whether the propulsion of the flutter kicks is exerted during front crawl swimming. In recent years, the propulsion during swimming has been estimated by combining pressure distribution measurements and three-dimensional motion analysis. In the propulsion estimation method using three-dimensional motion analysis and pressure distribution measurement, the hand/foot propulsion is estimated from the pressure difference between the palmer (planter) and dorsul side and the orientation of the hand/foot. Studies have been conducted to estimate hand propulsion in front crawl swimming and foot propulsion in breaststroke and eggbeater kick. Although this methodology has not been used for the flutter kicks so far, we believe that the methods used for breaststroke and eggbeater kick can be applied. Therefore, the purpose of this study was to clarify the factors that increase swimming velocity by using the flutter kicks by measuring hand and foot propulsion with and without the kick.